The role of income in energy efficiency and curtailment behaviours: Findings from 22 European countries. (July 2019) - Umit, Resul; Poortinga, Wouter; Jokinen, Pekka; Pohjolainen, Pasi
Abstract: Reducing consumers' demand for energy is on the agenda of various energy and climate policies. Although these policies are increasingly internationalised in Europe, our understanding of consumers' energy saving behaviour remains fragmented with often contradicting findings from single case studies. Drawing on the latest round of the European Social Survey across 22 countries ( n = 41, 830), we find that many variables have the same relationship with different energy saving behaviours, except household income. While income correlates positively with the likelihood of buying energy efficient appliances, it correlates negatively with the frequency of engaging in energy curtailments. If income has a differentiating effect on consumers' energy saving behaviour, then the demand reduction policies that take this difference into account will be more successful.